1979
DOI: 10.1111/j.1471-4159.1979.tb00384.x
|View full text |Cite
|
Sign up to set email alerts
|

CHARACTERISTICS OF GLUTAMINE vs GLUTAMATE TRANSPORT IN ISOLATED GLIA AND SYNAPTOSOMES

Abstract: Abstract— The uptake of the neurotransmitter candidates glutamate and aspartate into synaptosomes and bulk‐isolated glia was considerably more rapid than the uptake of the suspected transmitter‐precursor glutamine at low concentrations (10 μM). Glial uptake in all cases was one‐fifth to one‐third of synaptosomal, whereas isolated neurons attained very low tissue: medium ratios, probably reflecting damage to the neurons sustained during isolation. The glial and synaptosomal uptakes of glutamate both obeyed dual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
21
1
2

Year Published

1982
1982
2000
2000

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(28 citation statements)
references
References 25 publications
4
21
1
2
Order By: Relevance
“…The observed pharmacologic profile of [3H]EAA uptake in striatum and cerebellum was generally consistent with previous reports Johnston, 1972, 1973;Bennett et al, 1973;Balcar et al, 1976;Johnston et al, 1979;Weiler et al, 1979;Vincent and McGeer, 1980;Marvizon et al, 1981;Naito and Ueda, 1985;Shousboe et al, in press]. Further, within a single region of brain, no marked differences were noted in the potency of compounds to inhibit [3H]EAA uptake.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The observed pharmacologic profile of [3H]EAA uptake in striatum and cerebellum was generally consistent with previous reports Johnston, 1972, 1973;Bennett et al, 1973;Balcar et al, 1976;Johnston et al, 1979;Weiler et al, 1979;Vincent and McGeer, 1980;Marvizon et al, 1981;Naito and Ueda, 1985;Shousboe et al, in press]. Further, within a single region of brain, no marked differences were noted in the potency of compounds to inhibit [3H]EAA uptake.…”
Section: Discussionsupporting
confidence: 90%
“…Both high-and low-affinity uptake systems for GLU and LASP have been demonstrated in brain. High-affinity mechanisms, thought to be synaptically relevant, are temperature-dependent, regionally distributed in brain, enriched in synaptosomal fractions, and driven by a transmembrane sodium gradient [Bennett et al, 1973;Davies and Johnston, 1976;Balcar et al, 1976;Campbell and Shank, 1978;Weiler et al, 1979;Marvizon et al, 1981;Erecinska et al, 1983;Naito and Ueda, 19851. Whether exogenously accumulated GLU and LASP contribute to neurotransmitter pools of EAAs is not clear. Uptake systems for GLU and LASP are present on both neuronal and glial elements [Bennett et al, 1973;Balcar et al, 1976;Campbell and Shank, 1978;Marvizon et al, 1981;Erecinska et al, 1983;Naito and Ueda, 1985;Garthwaite and Garthwaite, 1985;Schousboe et al, in press].…”
Section: Discussionmentioning
confidence: 98%
“…This may reflect the difference in glutamine uptake by mitochondria as compared to synaptosomes [Weiler et al, 1979;Besagni et al, 1981;Minn, 19821. It should be noted that rates of I4CO2 production would be greatly affected by metabolic pool size and the observed differences in rates of oxidation by the subfractions may be due to differences in metabolic pool size between these two subcellular organelles. These data indicate that glutamine oxidation is also regulated differently by these two subcellular organelles and may reflect metabolic compartmentation [Balazs and Cremer, 1973;Berl et al, 19751.…”
Section: Discussionmentioning
confidence: 97%
“…They can also function over a broad pH range and, in some situations, mediate amino acid release more than uptake (35,36). Kinetic studies have shown that distinct transport systems exist for glutamine in neurons and astrocytes (37)(38)(39). Uptake of glutamine by rat cerebellar granule cells, a predominantly glutamatergic nerve cell population, is primarily mediated by system A (40).…”
mentioning
confidence: 99%